Liver-draining portal lymph node responds to enteric nematode infection by generating highly parasite-specific follicular T helper and B cell responses - Adjah, Joshua; D. Musimbi, Zaneta; Mugo, Robert M.; Midha, Ankur; Hartmann, Susanne; Rausch, Sebastian (Frontiers in Immunology, 2025)
IntroductionWhile research on the gut-liver axis in non-communicable liver diseases has expanded exponentially, few studies have investigated the liver-gut relationship in the context of gastrointestinal nematode infections. This study aimed to determine whether liver-draining lymph nodes (LLNs) contribute to the immune response against a strictly enteric nematode infection.MethodsWe analyzed the cellular and functional immune responses in the portal (PLN) and celiac (CLN) liver-draining lymph nodes following infection with the small intestinal nematode Heligmosomoides (polygyrus) bakeri (H. bakeri). The composition of dendritic cells and CD4+ T cell subsets in LLNs was compared to the mesenteric lymph nodes (MLN), the primary draining site of gut infections. Additionally, we examined Th2 effector cell expansion, plasmablast generation, and B cell activation across these lymphoid sites.ResultsBoth PLN and CLN exhibited increased cellularity at d14 post-infection. The immune profile in CLN closely resembled that of MLN, characterized by a robust expansion of GATA-3+ Th2 effector cells at days 6 and 14 post-infection. This was accompanied by an early plasmablast response, producing low-affinity IgG1 antibodies targeting immune-dominant excretory-secretory (ES) products. In contrast, PLN showed weaker Th2 responses and lower early plasma cell responses compared to MLN and CLN. However, PLN displayed strong follicular T helper (TFH) activity, with a B cell profile biased toward germinal center reactions. This led to high-affinity IgG1 antibodies specifically binding VAL-1 and ACE-1.DiscussionThese findings demonstrate, for the first time, that liver-draining lymph nodes actively participate in the adaptive immune response to enteric nematode infections. While MLN and CLN function synergistically in generating early Th2 effector cells and rapid extrafollicular IgG1+ plasma cell responses, PLN specializes in TFH-driven germinal center reactions and affinity maturation.